1987
DOI: 10.1007/bf00055258
|View full text |Cite
|
Sign up to set email alerts
|

The chromosomes of Nycticebus coucang (Boddaert, 1785) (Primates: Prosimii)

Abstract: The high-quality karyotype of a specimen of Nycticebus coucang is described and illustrated. The X chromosome is found to be indistinguishable from that of the greater galagos, and may represent a synapomorphic trait. The y chromosome is a medium to small submetacentric (3.2% TCL) and constitutes one of the larger Y chromosomes known in primates. N. coucang is found to have multiple NOR-bearing chromosomes in contrast to the single pair found in galagine and catarrhine monkeys. Since a single NOR-bearing pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
5
15
0
Order By: Relevance
“…1 ). Since the DAPI-band pattern is similar to those of G-bands, we were able to compare our results with G-banded karyotypes previously described for the closely related species N. coucang [Stanyon et al, 1987;Nie et al, 2006]. The karyotypes of these species were very similar to each other ( fig.…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…1 ). Since the DAPI-band pattern is similar to those of G-bands, we were able to compare our results with G-banded karyotypes previously described for the closely related species N. coucang [Stanyon et al, 1987;Nie et al, 2006]. The karyotypes of these species were very similar to each other ( fig.…”
Section: Resultsmentioning
confidence: 50%
“…1 , 2 ). The results suggest that N. bengalensis experienced a higher genomic dispersion of rDNA in its evolutionary history than N. coucang , N. pygmaeus, or N. intermedius [Stanyon et al, 1987;Cheng et al, 1993;Warter and Rumpler, 1998]. Multiple manifestations of rDNA loci, in turn, suggest a mechanism of ectopic recombination through association of rDNA and other chromosomal segments during cell division ( fig.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although lorisiform primates are distributed in both Asia and Africa, they are considered a monophyletic group and share a common ancestry based on fossil records, morphology, behavior, and molecular studies (Rasmussen and Nekaris, 1998). Previous conventional karyotypic analyses indicated that lorisiform primates probably evolved from a common ancestor with a diploid number of 2n ¼ 62, and that its karyotype was similar to that of the greater bushbaby (Otolemur crassicaudatus, OCR, 2n ¼ 62) (de Boer, 1973a-c;Dutrillaux, 1979;Dutrillaux et al, 1982;Rumpler et al, 1983Rumpler et al, , 1987Master et al, 1987;Stanyon et al, 1987). An earlier chromosomal phylogeny, based on comparative banding analysis, suggests that the 2n ¼ 50 karyotype of slow loris (Nycticebus coucang, NCO) evolved from the 2n ¼ 62 ancestral lorisiform karyotype via nine pericentric inversions, seven interchromosomal rearrangements, and the acquisition of heterochromatin on nine chromosomes (Rumpler et al, 1987).…”
mentioning
confidence: 96%